Belief in Superstition and Intolerance in Conditions of Uncertainty - Pamardisiwi, Tiara Awanisa; Muhammad, Amri Hana (Journal of Social and Industrial Psychology, 2023)
The condition of intolerance to uncertainty in individuals arises when there is a possibility of a bad situation or having a risky future. Therefore, many individuals try to reduce these adverse effects that may occur in the future by believing in superstitions. This research will reveal whether there is a superstitious belief in intolerance in uncertain conditions. Data will be analyzed using Pearson Product Moment involving 395 subjects selected through quota sampling. The results showed that there was a relationship between superstitious beliefs and intolerance of uncertainty with a correlation strength of 0.423. This means that when an individual is in an uncertain situation, it can trigger the presence of intolerance of uncertainty. On the other hand, the presence of superstitious belief is believed to have existed in the individual and tends to be used as a protector in making decisions.